Bushenhuoxue formula attenuates cartilage degeneration in an osteoarthritic mouse model through TGF-β/MMP13 signaling - Wang, Ping-er (J Transl Med, 2018)
BACKGROUND: Articular cartilage degeneration plays a key role in the pathogenesis of osteoarthritis (OA). Bushenhuoxue formula (BSHXF) has been widely used in the treatment of OA in clinics. However, the molecular mechanisms responsible for the chondroprotective effect of BSHXF remain to be elucidated. The purpose of this study was to explore the effects of BSHXF on OA mice model. METHODS: In this study, we investigated the effects of BSHXF on destabilization of the medial meniscus (DMM)-induced chondrocyte degradation in OA mice model. At 12 weeks post-surgery, the joints were harvested for tissue analyses, including histology, histomorphometry, TUNEL, OARSI scoring, micro-CT and immunohistochemistry for COL2, TGFBR2, pSMAD2 and MMP13. Additionally, we also evaluated the effects of BSHXF on Mmp13 mRNA and protein expression in chondrogenic ATDC5 cells through real-time PCR and Western blot respectively. Moreover, we investigated the chondroprotective effect of BSHXF on mice with Tgfbr2 conditional knockout (Tgfbr2(Col2ER) mice) in chondrocyte, including the relative experiments mentioned above. We transfected Tgfbr2 siRNA in ATDC5 to further evaluate the changes of Mmp13 mRNA and protein expression followed by BSHXF treatment. RESULTS: Amelioration of cartilage degradation and chondrocyte apoptosis were observed in DMM-induced mice, with increases in cartilage area and thickness, proteoglycan matrix, COL2 content and decreases in OARSI score at 12 weeks post surgery. Moreover, the elevated TGFBR2 and pSMAD2, and reduced MMP13 positive cells were also revealed in DMM-induced mice treated with BSHXF. Besides, decreased Mmp13 mRNA and protein expression were observed inchondrogenic ATDC5 cells culture in serum containing BSHXF. As expected, Tgfbr2(Col2ER) mice exhibited significant OA-like phenotype. Interestingly, obvious improvement in articular cartilage structure was still observed in Tgfbr2(Col2ER) mice after BSHXF treatment via up-regulated pSMAD2 and down-regulated MMP13 expressional levels in articular cartilage. CONCLUSIONS: BSHXF could inhibit cartilage degradation through TGF-β/MMP13 signaling, and be considered a good option for the treatment of OA.